The role of emotions in ontological conflicts: a case of study of the territorial–ontological conflict between British Columbia, Coastal GasLink and the Wet’suwet’en - B.A. Gálvez-Campos (Global Social Challenges Journal)
Drawing on a methodological approach that involved visual ethnography and combined content and narrative analysis, my research aims to analyse the role that emotions play in the territorial–ontological conflict between British Columbia provincial government, Coastal GasLink and the Wet’suwet’en. Using high-quality online audiovisual material produced by the Wet’suwet’en – allowing a critical perspective throughout the article on the politics of self-representation – I was able to get into the conflict with a phenomenological approach, employing my senses to analyse body movements, tone of voice and language. Theoretically, I articulate a framework made up of Ingold’s phenomenology, Blaser’s ontological conflicts and Escobar’s studies of culture. Then, I build on the spiderweb, a metaphor developed by Ingold, to expand the scope of González-Hidalgo’s emotional political ecologies. The results show that Coastal GasLink, taking culture ‘as a symbolic structure’, proposes as a central mitigation strategy, through their environmental impact assessment, what I call ‘an ontological interruption’ of the Yintakh. Besides, I demonstrate that the processes of political inter-subjectivation sought at the Unist’ot’en Healing Centre help understand the worry, frustration and stress of the Wet’suwet’en facing the world-creating practices of Coastal GasLink. On the other hand, the Healing Centre also reveals how the affections for the other-than-human and their spiderweb (Yintakh or relational world) inform Wet’suwet’en resistance. Lastly, I unveil how Coastal GasLink and the Ministry of Aboriginal Rights, through practices of inclusion and gender equality, seek to blur radical cultural differences, delegitimise the Wet’suwet’en precolonial governance system, and create affections for the Western-modern world.